PENINGKATAN KEMAMPUAN MENULIS ARTIKEL ILMIAH POPULER SISWA KELAS IX SMP NEGERI I BRINGIN DENGAN PEMBELAJARAN SAINTIFIK BERBASIS MEDIA MASSA - Sukardi Ks; Bambang WR; Indah Sugiyarti (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2016)
The research aimed at knowing to what extent (1) the effectiveness of Mass Media Based Scientific Approachas to improve the ability to write popular scientific articles, (2) the improvement ofNinth Junior High students? activity, enthusiasm, concentration and creativityin the learning process, and (3) the improvement of Ninth Junior High students? achievement in writing popular scientific article at Negeri 1 Bringin Semarang District after the implementation of mass media based scientific approach. It was a classroom action research (PTK), consisting of components of planning, implementation, observation, and reflection. It included two cycles. The first cycle was implenting scientific approach by utilizing the video